The moderator effects of cardiovascular risks on the determinant factors of autonomy, perceived behavioural control and motivation towards the physical activity levels among elderly in Kuala Lumpur - Kishenthi Kerisnan, Zulhabri Othman, Norshafarina Shari, Lilik Herawati (South Eastern European Journal of Public Health, 2025)
Introduction/Aims: The elderly with or without cardiovascular disease (CVD), also vary in their physical, behavioural, cognitive, and health status, gender, personality, and emotional handling, all of which are factors for the elderly involving physical activity (PA). This study aims to explore the PA level of the elderly in Kuala Lumpur by evaluating the determinant factors based on the moderating effect of CVD risk factors. Methodology: A quantitative study was performed on 400 elderly from several elderly care centres in Kuala Lumpur. The questionnaire sections include demographics, PA tests, and CVD risk factors using Framingham Risk Score (FRS). The questionnaires on determinant factors include self-efficacy, social support, attitude, perceived behaviour control (PBC), autonomy, and motivation. SPSS analysis was used to test the hypothesis of this study. Results: There were significant differences (F=4.92; p=0.008) between the CVD risk factors and physical activity level. The analysis has shown the effect of the CVD risk factors towards the physical activity level among the elderly in Kuala Lumpur. The independent t-test has shown significant differences (t=5.59; p<0.0001) in CVD risk factors between genders. The CVD risk factors have been shown to be higher in males compared to females. The multiple regression analyses showed that the moderator variable of CVD risk factors moderating the association of independent variables of motivation (F=5.382; p=0.001), autonomy (F=4.709; p=0.014) and perceived behavioural control (PCB) (F=4.709; p=0.014) towards the dependent variable of physical activity (PA) levels among the Kuala Lumpur’s elderly population. Whereas the analysis showed that the independent variables of self-efficacy, social support, and attitude did not support the hypothesis for predicting physical activity level. Conclusion: The determinant factors of motivation, perceived behavioural control, and autonomy were suggested as the strongest variables and positively related to the physical activity engagement among elderly in Kuala Lumpur. The current study emphasises the significance of identifying determinant factors and how they influence older adults' participation in physical activity.